2016
DOI: 10.1515/jvetres-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant defence markers in muscle tissue of rainbow trout (Oncorhynchus mykiss) after vaccination against Yersinia ruckeri

Abstract: Introduction: The goal of this study was to assess the influence of vaccination against enteric redmouth disease on oxidative stress biomarkers and antioxidant defence in the muscle tissue of rainbow trout (Oncorhynchus mykiss Walbaum) vaccinated against Yersinia ruckeri in the first and second month after immunisation. Material and Methods: Healthy fish were vaccinated orally with inactivated whole cells of a virulent strain of Y. ruckeri. One and two months after immunisation the muscle samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…This smaller increase in NO and MDA levels in group IV compared to group III is thought to have been caused by the antioxidant effect of dexpanthenol. It has been reported that oxidative stress parameters such as NO and MDA increase in inflammatory conditions (1,2,13,18,22). It was detected that NO, MDA and TOC levels increased significantly in group III at day 5 compared to the levels at day 0 (p ≤ 0.001), and TAC decreased at a statistically significant level (p = 0.028).…”
Section: Tab 3 Distribution Of Serum No (µMol/l G Wet Tissue) Mda mentioning
confidence: 78%
“…This smaller increase in NO and MDA levels in group IV compared to group III is thought to have been caused by the antioxidant effect of dexpanthenol. It has been reported that oxidative stress parameters such as NO and MDA increase in inflammatory conditions (1,2,13,18,22). It was detected that NO, MDA and TOC levels increased significantly in group III at day 5 compared to the levels at day 0 (p ≤ 0.001), and TAC decreased at a statistically significant level (p = 0.028).…”
Section: Tab 3 Distribution Of Serum No (µMol/l G Wet Tissue) Mda mentioning
confidence: 78%
“…MDA is used as a marker for the oxidation of membrane phospholipids through lipid peroxidation. [27][28][29][30][31][32][33][34] The antioxidant defense system consists of antioxidant enzymes, such as SOD, CAT, GPx, and GR, and low molecular weight antioxidants, such as reduced glutathione, vitamin A, vitamin C, and vitamin E. Antioxidant levels can be used as an indicator of the antioxidant status of the organism and can act as biomarkers of oxidative stress. When antioxidant defenses are broken or exceeded, oxidative stress can cause DNA damage, enzymatic inactivation, and peroxidation of cell components, especially lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was determined that there was a significant increase in SOD activity after 30 days but a decrease after 60 days. As a result, it has been found that the Yersinia vaccine is partially responsible for the induction of increased protective immunity against Y. ruckeri infection 33 Tkachenko et al 34 administered a vaccine against Y. ruckeri for trout in their study and examined the changes in lipid peroxidation level and SOD, CAT, GR, and GPx activities in fish gill, heart, and liver tissues four weeks after the administration of the vaccine. As a result of the study, they determined that each tissue shows its own specific oxidative stress response.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanizm potęgowania reakcji adaptacyjnej układu immunologicznego przez stres oksydacyjny w przeciwieństwie do ssaków jest mało poznany u ryb. Niejednokrotnie wykazano, że eksperymentalne podanie LPS u zwierząt doświadczalnych (myszy i szczurów), a także immunizacja pstrągów przeciwko jersiniozie i wrzodzienicy indukują stres oksydacyjny (1,3,32,33). Dotychczasowe badania u ryb wykazały silne działanie immunostymulujące lipopolisacharydu manifestujące się między innymi wzrostem aktywności metabolicznej komórek fagocytujących wskazujących na wystąpienie "wybuchu tlenowego" (10,25,28).…”
Section: Praca Oryginalnaunclassified
“…Znaczący wzrost aktywności po 3, 6 i 12 godzinach SOD w erytrocytach i po 3 i 6 godzinach w fagocytach może być reakcją adaptacyjną na immunizację LPS, a także wpływem LPS na ekspresję genów dysmutazy ponadtlenkowej (27). Podobny efekt zwiększonej aktywności SOD stwierdzono w tkankach ryb po podaniu szczepionek (32,33) i po ekspozycji na ksenobiotyki (24, 34, 36). Obserwowany w badaniach późniejszych Objaśnienia jak w tab.…”
Section: Wyniki I Omówienieunclassified